Devastation of aquifers from tsunami‐like storm surge by Supertyphoon Haiyan. Issue 8 (28th April 2015) - Cardenas, M. Bayani; Bennett, Philip C.; Zamora, Peter B.; Befus, Kevin M.; Rodolfo, Raymond S.; Cabria, Hillel B.; Lapus, Mark R.
Abstract The northwest Pacific Ocean is a hot spot for sea level rise and increasing frequency of stronger storms. It is where Supertyphoon Haiyan formed, the strongest storm to hit land, which provided a window into the hydrologic impacts of an extreme storm. Through detailed documentation of flood levels, groundwater table elevations and salinity, electrical resistivity, and modeling, we found that Haiyan's storm surge reached 7 m above sea level along Samar Island, Philippines, which led to contamination of crucial aquifers by infiltrating seawater. A contaminated surficial aquifer will take years to recover. Groundwater in an underlying deeper aquifer saw widespread contamination immediately after the storm, but here salinity has decreased significantly after 8 months. However, this deeper aquifer remains vulnerable to seawater slowly percolating through the surficial aquifer. As warmer seas generate more powerful storms, the vulnerability of aquifers to persistent contamination from intense storm surges is a growing concern for coastal communities.